LIFE-DEATH PROBLEM IN CULTURE OF PRE-INDUSTRIAL SOCIETY - Anna S. Lycheva (Advanced Engineering Research)
Attitude towards life - death during the antiquity and in the Middle Ages is considered. The comparative analysis of these phases of history is given. The author presents a number of reasons to explain the established attitude towards life and death in the given cultures.